Bis 4-(dimethylamino)pyridinium tetrabromidobis(4-methylphenyl) stannate(IV) - Lee, S.M.; Robinson, W.T.; Ali, Hapipah Mohd; Lo, K.M. (International Union of Crystallography, 2009)
In the title compound, (C7H11N2)(2)[SnBr4(C7H7)(2)], the tetrabromidobis(4-methylphenyl) stannate(IV) anion possesses a centre of inversion located at the Sn-IV atom. In the crystal structure, two inversion-related cations are linked to the anion via weak N-H center dot center dot center dot Br hydrogen bonds.